Health promotion and communication activities in Al Islam Hospital Bandung - Dewi, Retasari; Anisa, Renata; Yustikasari, Yustikasari; Safi, Abdul Qayoum (Jurnal Kajian Komunikasi, 2024)
Background: Health promotion is an important part of the health services strategy in hospitals around the world, including in Indonesia. Hospitals can contribute to improving Indonesians’ health by complying with regulations and following government plans. Al Islam Hospital is a type B hospital in Bandung that has adopted diverse health promotion and communication programs. RS Al Islam Bandung is committed to improving the community’s health status through various programs. Purpose: This study aimed to understand how the hospital’s health promotions (PKRS) installation implements advocacy, community empowerment, and partnership programs through communication activities and media. Methods: We employed a qualitative method that included interviews, observation, and a review of relevant literature. Results: The results showed that RS Al Islam Bandung had integrated the principles of effective health communication into its PKRS program. Firstly, hospital management engages in health advocacy by issuing policies in various media that support health promotion programs; secondly, Al Islam Bandung Hospital equips the community with the information, willingness, and skill necessary to tackle the different health issues by involving patients and their families, hospital human resources, and the community; and thirdly, RS Al Islam Bandung establishes collaboration with educational institutions, local communities, and mass media. Conclusion: For the sustainability and effectiveness of health promotion programs, hospitals must ensure continued cooperation with stakeholders and continue to improve their health communication media. Implication: The study suggests that hospital management can conduct a continuous evaluation of health promotion activities carried out at Al Islam Bandung Hospital so that the health promotion and communication activities are not limited to the hospital area. The hospital can achieve this by optimizing its communication media. Hospitals can start using social media analytics and SEO campaigns to produce messages that cater to the needs of their audience.